اختبار العلاقة بين نظام سعر الصرف والنمو الاقتصادي في الجزائر دراسة قياسية (1980-2020) باستخدام نموذج Ardl - ايبو, وهيبة; يبرير, محمد (جامعة الوادي - University of Eloued, 2022)
This study aims to identify the impact of the exchange rate regime on Algeria's economic growth and to determine the nature of their relationship, based on a standard study using the ARDL model, and annual data for the Algerian economy covering the period (1980-2020), and also relied on the factual classification of (Ilzetzki Ethan, Carmen M. Reinhart and Kenneth Rogoff2019), and We have found that there is no significant relationship between Algeria's de facto exchange rate regime and economic growth, and a significant relationship between both investment, trade openness and final expenditures for government consumption and economic growth, that is, Algeria's exchange rate regime indirectly affects economic growth by influencing its determinants
Test of the relationship between the exchange rate regime and economic growth in Algeria Standard study (1980-2020) using the ARDL model
مقال
Keywords: نظام سعر الصرف؛ النمو الاقتصادي؛; ARDL